Sosialisasi Pendidikan Karakter Anak dengan Media Kartun Bocah Hutan Mowglu dan Goldilocks di KB Ceria Kartasura Sukoharjo Jawa Tengah - Nurul Ilmi Azizah, Annafi; Cholisa Nadhifa, Avida; Lailatul Rohimah, Qori; Mutmainah, Fitri; Harnanto, Tantrianti; Shohwah, Izzathush; Melia Tamsir, Jenny; Durrotun Nafisah, Nona; Irma Fernanda, Dera (Mulya Literasi Publishing, 2024)
Character education is an essential component in the development of early childhood, playing a role in shaping morals, social skills, and self-confidence. This community service aims to socialize character education through the media of the cartoon films